An Explorative Study on Monocyte Reprogramming in the Context of Periodontitis In Vitro and In Vivo - Noz, Marlies P.; Plachokova, Adelina S.; Smeets, Esther M.M.; Aarntzen, Erik H. J. G.; Bekkering, Siroon; Vart, Prya; Joosten, Leo A. B.; Netea, Mihai G.; Riksen, Niels P. (Frontiers in Immunology, 2021)
Aims Periodontitis is an independent risk factor for cardiovascular disease, but the mechanistic link is not fully understood. In atherosclerotic cardiovascular disease, monocytes can adopt a persistent hyperresponsive phenotype, termed trained immunity. We hypothesized that periodontitis-associated bacteria can induce trained immunity in monocytes, which subsequently accelerate atherosclerosis development. Materials and methods We combined in vitro experiments on human primary monocytes and in vivo techniques in patients with periodontitis to test this hypothesis. Adherent peripheral blood mononuclear cells (PBMCs) were transiently exposed in vitro to Porphyromonas gingivalis for 24 hours, and restimulated with lipopolysaccharide (LPS) or Pam3CysK4 (P3C) six days later, to measure interleukin-6 (IL-6) and tumor necrosis factor α (TNFα) production. In an exploratory observational study, patients with severe periodontitis (63±6 years, n=14) and control subjects with no-to-mild periodontitis (54±10 years, n=14) underwent venepuncture and 2’-deoxy-2’-[18F]fluoro-D-glucose positron-emission-tomography ([18F]FDG PET/CT) scanning. Results When adherent peripheral blood mononuclear cells (PBMCs) were transiently exposed in vitro to Porphyromonas gingivalis for 24 hours, and restimulated with LPS or P3C six days later, IL-6 and TNFα production was significantly increased (TNFα/P3C, p<0.01). Circulating leukocytes, IL-6 and interleukin-1 receptor antagonist (IL-1Ra) concentrations were generally higher in patients compared to controls (leukocytes: p<0.01; IL-6: p=0.08; IL-1Ra: p=0.10). Cytokine production capacity in PBMCs after 24h stimulation revealed no differences between groups. [18F]FDG PET/CT imaging showed a trend for increased [18F]FDG-uptake in the periodontium (mean standard uptake value (SUVmean), p=0.11) and in femur bone marrow (SUVmean, p=0.06), but no differences were observed for vascular inflammation. Positive correlations between severity of periodontitis, measured by The Dutch Periodontal Screening Index and pocket depth, with circulating inflammatory markers and tissue inflammation were found. Conclusions P. gingivalis induces long-term activation of human monocytes in vitro (trained immunity). Patients with severe periodontitis did have signs of increased systemic inflammation and hematopoietic tissue activation. However, their circulating monocytes did not show a hyperresponsive phenotype. Together we suggest that trained immunity might contribute to local periodontal inflammation which warrants further investigation.